1976
DOI: 10.1073/pnas.73.4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of mouse DNA polymerase-alpha.

Abstract: Although DNA polymerase-a (DNA nucleotidyltransferase; deoxynucleoside triphosphate:DNA deoxynucleotidyltransferase; EC 2.7.7.7) probably functions in the nucleus, it is usually found predominantly in the nonnuclear fraction of disrupted cells. We have reexamined the intracellular location of this enzyme using cytochalasin-B-induced enucleation, a technique which avoids exposure of nuclei to extra-cellular conditions during cell fractionation. In conditions where viability of separated cell parts is high and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…We are unable to detect DNA polymerase a in the nucleus. The conclusion drawn in this study differs quantitatively from that of Herrick et al (7). These investigators showed that 88% of total DNA polymerase a was present in their karyoplast fraction.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…We are unable to detect DNA polymerase a in the nucleus. The conclusion drawn in this study differs quantitatively from that of Herrick et al (7). These investigators showed that 88% of total DNA polymerase a was present in their karyoplast fraction.…”
Section: Discussioncontrasting
confidence: 97%
“…By examining the distribution of DNA polymerase a in fractions derived from cytochalasin enucleation of mammalian cells, we show that DNA polymerase a present in the crude karvoplast fraction is perinuclear in origin. Assaying for DNA polvmerase a activity in extracts made from karyoplasts after simple enucleation procedures (7,16) cannot distinguish between a perinuclear and an intranuclear location of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of T7 lane c, the bands produced by RNase HI correspond to the T7 mRNA species previously observed (19) (20,31); and (iv) an RNase P, which, like that reported in KB cells (12) (33). Finally, the DNA polymerase a, initially recovered from the cytoplasm of various cell types (34), has more recently been found in association with the nucleus (35). Thus, although it appears that subcellular fractionation of eukaryotic cells may not preserve the in vivo distribution of enzymes involved in nucleic acid metabolism, this situation does not necessarily impede their study.…”
Section: Methodssupporting
confidence: 72%
“…For example, by a detergent method, DNA polymerase is found in the cytoplasm. However, by the cytochalasin B technique, this enzyme activity is found to be associated with the nucleus (3). The cytochalasin B technique has the additional feature in that the cytoplasm can be recovered in intact particles, the cytoplasts.…”
mentioning
confidence: 99%